2007
DOI: 10.1007/s10735-007-9103-8
|View full text |Cite|
|
Sign up to set email alerts
|

GABA and glutamate signaling: homeostatic control of adult forebrain neurogenesis

Abstract: SummaryThe neurotransmitter GABA exerts a strong negative influence on the production of adult-born olfactory bulb interneurons via tightly regulated, non-synaptic GABAergic signaling. After discussing some findings on GABAergic signaling in the neurogenic subventricular zone (SVZ), we provide data suggesting ambient GABA clearance via two GABA transporter subtypes and further support for a non-vesicular mechanism of GABA release from neuroblasts. While GABA works in cooperation with the neurotransmitter gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 66 publications
(72 reference statements)
2
35
0
1
Order By: Relevance
“…The pattern of immunoreactivity directed to GAD and GABA in the RMS has previously been documented (Platel et al 2007). In addition to the numerous differentiating cells immunoreactive with both GAD 65/67 and GABA antisera, scattered MNs somata were also found throughout the bulbar core (Fig.…”
Section: Immunohistochemistrymentioning
confidence: 83%
See 1 more Smart Citation
“…The pattern of immunoreactivity directed to GAD and GABA in the RMS has previously been documented (Platel et al 2007). In addition to the numerous differentiating cells immunoreactive with both GAD 65/67 and GABA antisera, scattered MNs somata were also found throughout the bulbar core (Fig.…”
Section: Immunohistochemistrymentioning
confidence: 83%
“…Indeed, GABA, an inhibitory neurotransmitter in the adult central nervous system, provokes GABAAreceptor-mediated depolarization in neuronal precursors in the subventricular zone (Wang et al 2003;Farrant and Nusser 2005). Additionally, subventricular zone neuronprogenitors bind anti-GABA antibodies; therefore, GABA is assumed to exert negative feed-back against astrocyte proliferation (Platel et al 2007). One feature relevant for the present study is that GABA influences cell proliferation (LoTurco et al 1995) and promotes cell migration (Behar et al 1996(Behar et al , 1998 and physiological differentiation (Kelsch et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Long term morphogenetic influence on the differentiation of target neurons and expression of a specific phenotype was shown in studies on mam mals (Ugrumov, 2009;. It was shown that mole cules of neurotransmitters have a significant impact on the development of cells during embryogenesis (Platel et al, 2007), as well as in the course of postembryonic neurogenesis of the subgranular zone of the dentate gyrus of the medial and lower surface of the brain hemisphere (Cameron et al, 1995;Aniol, Stepan (Aniol, Stepanichev, 2007;Platel et al, 2010). The results of our studies allow us to assume that in the diencephalon and medulla oblongata of the masu salmon, TH, GABA, and NADPH d can play the role of signal molecules, which regulate the processes of adult neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult mammalian brain, the two adult neurogenic regions include the SVZ and the SGZ in the hippocampus, which contain the pool of dividing neural stem cells (Platel et al 2007). SVZ astrocytes have stem cell attributes while radial-type astrocytes are also thought to have stem cell characteristics in the SGZ (Bordey 2006).…”
Section: Discussionmentioning
confidence: 99%